Achieving Work-Life Balance Among Millennial And Generation Z Employees: Challenges, Strategies, and Performance Implications - Evi Sulistiyani; Nuphanudin; Ainur Rifqi (Buletin Edukasi Indonesia, 2026)
Work-life balance has emerged as a critical concern in contemporary organizational management, particularly as Millennial and Generation Z employees increasingly constitute the dominant workforce demographic globally. Despite widespread recognition of work-life balance, younger workers continue struggling to achieve balance amid economic pressures, digital connectivity demands, and evolving workplace expectations. This research examines work-life balance dynamics among Millennial and Generation Z employees, investigating relationships between organizational support, work-life balance, and multiple performance outcomes, while exploring generational differences in these relationships and identifying specific challenges, strategies, and organizational factors influencing balance. This study employed a sequential explanatory mixed-methods design combining quantitative surveys and qualitative semi-structured interviews. The quantitative phase collected data from 478 employees (289 Millennials, 189 Generation Z) across five Indonesian cities using validated instruments measuring work-life balance, organizational support, job performance, satisfaction, and well-being. Structural equation modeling analyzed relationships and tested mediation effects, while multigroup analysis compared generational differences. The qualitative phase involved 32 in-depth interviews exploring lived experiences, challenges, and coping strategies, analyzed through thematic analysis using NVivo software. Organizational support significantly predicted work-life balance (β=0.61, p<0.001), which positively influenced task performance, contextual performance, job satisfaction, and well-being. Job satisfaction partially mediates work-life balance effects on performance outcomes. Generational differences emerged, with work-life balance more strongly predicting task performance (β=0.38 vs. β=0.22, p=0.032) and well-being (β=0.51 vs. β=0.36, p=0.041) for Generation Z compared to Millennials. Qualitative findings identified five major challenges: excessive workload, digital connectivity demands, financial pressures, organizational inflexibility, and career advancement tensions. Participants employed boundary management, technology limitations, prioritization skills, and social support mobilization as coping strategies. Work-life balance critically shapes performance outcomes among younger employees, with generational distinctiveness requiring nuanced organizational approaches. Organizations must move beyond symbolic policies to authentic cultural transformation supporting work-life balance, particularly addressing Generation Z's heightened needs while maintaining strong organizational support structures benefiting all employees.